THE LONG-TERM EFFECT OF FOREIGN DEBT AND FOREIGN DIRECT INVESTMENT (FDI) ON ECONOMIC GROWTH IN INDONESIA - Meilisa, Meilisa; Handra, Hefrizal; Yonnedi, Efa (Transpublika Publisher, 2024)
In light of Indonesia's status as a developing nation with constrained financial resources, the imperative for strategic decision-making by the government to foster sustained economic growth becomes evident. This research delves into an analysis of the enduring repercussions of foreign debt and foreign direct investment (FDI) on Indonesia's economic landscape. The study employs a comprehensive examination of time series data spanning from 1990 to 2022, employing both the Bounds test cointegration approach and the ARDL model to scrutinize the dynamics at play. The empirical findings underscore the multifaceted influence of foreign debt and FDI on Indonesia's economic growth, illustrating that these factors exert both short- and long-term impacts. Moreover, the research identifies the export control variable as a pivotal factor, indicating an immediate effect on Indonesia's economic development albeit without a lasting impact. Consequently, this unveils a nuanced interplay of variables that contribute to the nation's economic trajectory. In light of these insights, the study posits that the Indonesian government must adopt a judicious and discerning approach in formulating and executing policies related to exports, foreign debt, and FDI. Recognizing the dual temporal impact of foreign debt and FDI, policymakers are urged to balance short-term economic imperatives with a commitment to long-term sustainable growth. The immediate influence of the export control variable further underscores the need for agile and adaptive policy management to navigate the intricacies of Indonesia's economic landscape.